THU0175 DOSE-DEPENDENT RISK OF METHOTREXATE FOR RENAL IMPAIRMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Hayashi, Keigo; Sada, Kenei; Asano, Yosuke; Asano, Sumie Hiramatsu; Yamamura, Yuriko; Ohashi, Keiji; Morishita, Michiko; Watanabe, Haruki; Narazaki, Mariko; Matsumoto, Yoshinori; Kawabata, Tomoko; Wada, Jun
Abstract : Background: Methotrexate (MTX) is a mainstay in the therapy of rheumatoid arthritis (RA). It is recommended that MTX should be rapidly escalated to the maximum tolerated dose (16 - 30 mg/week) and tapering MTX can be considered after a persistent remission 1) . Renal impairment is one of the major concerns in treatment with high dose MTX for malignancy, but it is still unclear whether low dose MTX administration in RA cause the renal impairment or not. Objectives: The purpose of this study is to elucidate the association between MTX dosage and a one-year change of estimate glomerular filtration rate (eGFR) in RA patients. Methods: Of outpatients with RA in Okayama university hospital between 2006 and 2017, 497 patients who had continued the administration of MTX for more than one year were enrolled. All patients fulfilled the ACR/EULAR 2010 Classification Criteria for RA. Patients who had nephrotic syndrome, unilateral kidney or other rheumatic disorders other than secondary Sjögren's syndrome were excluded. The primary outcome was the change of eGFR during the most recent one year in each patient. The revised Japanese equation of Modification of Diet in Renal Disease 2) was used to calculate eGFR. MTX dosage was defined as an average dosage of MTX during the observational period. We evaluated the association between MTX dosage and the primary outcome using univariate and multivariate analysis. Results: Median (IQR) age was 64 (54 - 72) years, 78% were female, and median disease duration was 73 (31 - 160) months. The median dosage of MTX was 8 mg/week (6 - 10.1) and biological agents were used in 28% of the patients. The eGFR (mean ± SD) decreased by 1.2 ± 8.3 ml/min/1.73m2 in one year and MTX dosage was associated with the change of eGFR significant inversely (p<0.0001). The eGFR in patients treated with MTX <8 mg/week (n=185), ≥8 and <10 (n=131), ≥10 and <12 (n=86), ≥12 (n=95) decreased 0.2 ± 0.6, 0.6 ± 0.7, 1.0 ± 0.9, and 4.6 ± 0.8 ml/min/1.73m2/year, respectively. After adjusting possible confounding factors such as sex, age, concomitant use of NSAIDs, hypertension, and C reactive protein (CRP) using multiple linear regression analysis, MTX dosage was still an independent risk factor for the decrease of eGFR (beta-coefficient: -0.4, 95% confidence interval -0.12 - -0.61, p=0.003). Conclusion: Careful monitoring of renal function should be required in long-time treatment for RA patients with MTX. References: [1] Smolen JS, et al. Ann Rheum Dis. 2017;76:960-977. [2] Imai E, et al. Am J Kidney Dis. 2007;50:927-937. Disclosure of Interests: Keigo Hayashi: None declared, KENEI SADA Speakers bureau: Ken-Ei Sada received speaker honoraria from Chugai., Yosuke ASANO: None declared, Sumie Hiramatsu Asano: None declared, Yuriko Yamamura: None declared, Keiji Ohashi: None declared, Michiko Morishita: None declared, Haruki Watanabe: None declared, Mariko Narazaki: None declared, Yoshinori Matsumoto: None declared, Tomoko Kawabata: None declared, Jun Wada Grant/research support from: Jun Wada received grant support from Astellas, Bayer, Chugai, Daiichi Sankyo, Kissei, Kyowa Hakko Kirin, MSD, Otsuka, Teijin, Torii, Pfizer, Takeda, and Taisho Toyama., Speakers bureau: Jun Wada received speaker honoraria from Astellas, Boehringer Ingelheim, Novartis, and Tanabe Mitsubishi.